War and resilience: The multifaceted impacts of Sudan's conflict and pathways to recovery - Siddig, Khalid; Kirui, Oliver K.; Dorosh, Paul A. (International Food Policy Research Institute, 2026)
The synopsis is being made available in advance of an anticipated 2026 launch of the full book.